Morphology and Treatment of Tibial Fracture in Adult Patients at Teaching and Referral Hospital - Khan, Md Rukanuddawla; Badar Uddin, K M; Mozaherul Islam, Mohammed; Tosh Nath, Asho; Mazher Ali, Khandoker Muhammud; Chowdhury, Avijit; Molla, Tajuddin (Medicine Today, 2025)
Introduction with Objective: Tibia fractures are the most common long bone fractures in adult. The aim of the present study was to assess the morphology and treatment of tibial fracture in adult patients at a tertiary hospital. Materials and Methods: This Prospective Study was carried out among 48 patients attending at the department of Orthopedics Surgery at Chittagong Medical College Hospital, Chittagong for the treatment tibial fracture within the defined period from May 2022 to April 2023. Total 4 patients were dropped out in the middle of follow up. So follow up was done among 44 patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: Out of 48 patients, the mean ± SD age of the patients was 36.98 ± 8.240 years. Most of the patients (83.33%) were male. According to type of fracture, 45.8% patients had both 42A (1, 2, 3) and 42B (2, 3) type and 8.3% patients had 42C (3) type of fracture. Regarding location of fracture, 52.1% patients had proximal 1/3 of shaft fracture and 47.9% patients had middle 1/3 of shaft fracture of Tibia. Average mean ± SD duration of operation was 83.25 ±10.903 minutes (range: 60-110 minutes). Average mean ± SD fluoroscopy time was 110.48 ±10.078 seconds (range: 90-134 seconds). Average mean ± SD radiological union time was 3.44 ±0.841 months (range: 3-5 month). Average mean ±SD range of motion (ROM) was 110.00 ±2.753o (range: 105-115o) after 1 month, 120.66±5.048o (range: 113-128o) after 3 months, 124.11±4.260o (range: 118-130o) after 5 months and 128.11±3.294o (range: 123-133o) after 6 months. Average mean ±SD range of Lysholm knee score was 57.55 ±2.256 (range: 55-62) after 1 month, 67.00 ±3.941 (range: 60-73) after 3 months, 77.50 ±5.364 (range: 70-86) after 5 months and 86.64 ±5.545 (range: 72-95) after 6 months. After operation with itramedullary nail approach most of the patients (79.5%) functional outcome after six month was excellent. Conclusion: Treatment of tibial fracture was mainly surgical using locked intramedullary nail. Medicine Today 2025, Vol.37 (2): 214-217